ANALYSIS OF VIBRATION FREQUENCY RESPONCE CHARACTERISTIC METHOD STUDY - ZONG BangFei; CHU ChaoMei; HUANG YongHui; TAN Hui (Jixie qiangdu)
Aiming at the automobile gearbox shell local deformation failure problem,an evaluation method based on the dynamic stiffness of the critical point of the target shell is proposed. In a front transverse gearbox as the research object,using Hyperworks software to establish the finite element model of shaft hole in the key points of the incentive target the input method of transfer function,the vibration characteristics,vibration frequency analysis of vibration response of transmission after strong shell,obtained after the transmission housing mounting point acceleration frequency response curve and the frequency response curve of dynamic stiffness. Furthermore,the structure of the rear shell of the transmission is improved,and the improved structure is verified by software. Research shows that the dynamic stiffness of the frequency response curve evaluation method is an intuitive and accurate relationship with the deformation response of shell structure,can accurately find the effective method to frequency range and location of improved housing, and the housing structure improvement can effectively improve the vibration characteristics of the shell structure.